2020
DOI: 10.3389/fmicb.2020.01376
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Antibiotic Resistance: Are Current Approaches for Colocalizing Resistomes and Mobilomes Useful?

Abstract: Slizovskiy et al. Colocalization Analysis of Resistomes-Mobilomes that current alignment-and assembly-based methods estimating resistome mobility yield contradictory and incomplete results, likely constrained by approach-specific data inputs, and bioinformatic limitations. We discuss recent laboratory and computational advancements that may enhance resistome risk analysis in clinical, regulatory, and commercial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 110 publications
3
37
0
2
Order By: Relevance
“…Finally, it is acknowledged that metagenomic analysis is an evolving field, particularly for the characterization of antibiotic resistance in complex environmental samples [51,81,82]. Here we demonstrated that overall Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Finally, it is acknowledged that metagenomic analysis is an evolving field, particularly for the characterization of antibiotic resistance in complex environmental samples [51,81,82]. Here we demonstrated that overall Fig.…”
Section: Discussionsupporting
confidence: 59%
“…ARGs were annotated against the Comprehensive Antibiotic Resistance Database (CARD v1.0.6) [49] and plasmid-associated genes against the ACLAME database [50]. Given that differing annotation parameters and databases could produce different trends [51], resistomes of all samples were also annotated with DeepARG, which incorporates several publicly available databases and uses a deep learning algorithm to maximize ARG detection [47]. Relative abundances of total ARGs predicted by DeepARG were found to be strongly and significantly correlated with those annotated using CARD via MetaStorm, as described above (Fig.…”
Section: Metagenomic Sequencing and Analysismentioning
confidence: 99%
“…(2) These ARGs might be available at an undetected level before the treatment; however, danofloxacin administration might have favored horizontal gene transfer among genetically related and, probably, unrelated bacteria. Horizontal gene transfer is a common way of acquiring ARGs by bacteria in complex environments, such as in the gut [27,68,69]. Co-transfer of ermB and tetM in Streptococcus pyogenes was reported, which suggested their linkage in individual genetic elements [70].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the secondary effluent samples have higher mobilome diversity and composition does not immediately increase the potential of clinically relevant transfer risks to receiving environments, as these will be related to associations with AMR elements. Clearly significant numbers of resistome genes are either in plasmid-derived sequences or are associated with other mobile genetic elements, with implications for mobilization of antimicrobial resistance (Slizovskiy et al 2020).…”
Section: Effect Of Wastewater Treatment On the Resistome And Mobilomementioning
confidence: 99%